Українська точка біфуркації в епіцентрі геополітичного та світоглядного розлому між розпадом і буттям - Грушко, Віктор Сергійович; Hrushko, Viktor S. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Висвітлено проблеми сучасного українського суспільства, яке прагне осмислити себе, своє місце у світі та сенс існування. Розкрито особливості українського цивілізаційного пограниччя, де точиться боротьба різних світоглядів, способів пристосування до життя й самореалізації людини та соціуму. Зосереджено увагу на випробовуванні в регіоні якості ідей, народжених у цивілізаційному «тилу», проаналізовано їх взаємодію, трансформацію під впливом несприятливих умов, синтез відмінних форм організації суспільного життя й народження соціальних альтернатив. The article is devoted the problems of modern Ukrainian society which experiences the difficult period of comprehension itself and its own place in the world and filling with of the existence certain senses. Multidimensional wheels within wheels of social of Ukraine are in-process analyzed with the main centers of influence on it. Description of nature is given influencing on it for today forces and complication of their perception by Ukrainian society. Features open up Ukrainian civilization border where not only there is a fight of different world view universally, methods of adaptation, self-realization of man and social, but also simultaneously there is testing on durability of ideas bear in deep civilization a «rear», their co-operation, transformation under influence of unfavourable terms, synthesis of excellent forms of organization of public life, birth of social alternatives. The features of co-operation of different civilizations are analyzed, specifics of worldview contradictions and different conceptual doctrines of development of society in such difficult geopolitical knot as Ukraine. In addition Ukrainian society is examined simultaneously in the context of world processes and as the important all-sufficient world which comes forward not only the object of external influences but also as an epicenter of forming high-quality of new senses, principles of organization of public life, meaningful for humanity aims and priorities.
Ukrainian Point of Bifurcation in Epicentre Geopolitical and Worldview of Break a Secret between Disintegration and Life
Keywords: цивілізаційне прикордоння; соціальна самоорганізація; світоглядні універсалії; концептуальні стратегії розвитку суспільства; фінансова цивілізація; візантійська модель; civilization border; social universals; conceptual strategies of development of society; financial civilization; Byzantium models